Bauxite Residues ù A High Volume Resource - E Jamieson (The Australasian Institute of Mining and Metallurgy, 2004)
For a number of years, Alcoa World Alumina Australia (Alcoa) has been investigating opportunities to produce economically viable products from bauxite residues. Three of these potential products are described here, being Red Sand, ALKALOAM« and REDLIMETM.Red Sand has a nominal particle size of +100 micron and is physically little different to crushed bauxite from which it is derived. In AlcoaÆs Western Australian refineries, Red Sand constitutes up to half of the residue going to impoundment areas. Initial testing indicates that this sand could be processed to provide an acceptable general landfill material, a construction back fill or a material suitable for road base construction. ALKALOAM« is the fine-grained residue often referred to as red mud. A great deal of work has been done to show the benefits of adding this material to sandy soils, which are common in coastal regions of WA. ALKALOAM« has properties that can elevate the pH of the acidic soils and also retain phosphorous, reducing overall fertiliser use and protecting sensitive waterways. REDLIMETM is a by-product of the refining process. This material has a high acid neutralising value. REDLIMETM could be more effective at pH control than most available products because of the fine particle size and sodium carbonate that remains with the product.